Medical error: medical and legal definition - Титикало, Роман Сергійович; Гандзій, Тарас Васильович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
This paper examines the views of scholars on the definition of «medical error» and its causes, and studied the twin concepts of medical error: medical and legal.